Analisis Faktor-Faktor yang Mempengaruhi Pembiayaan Mudharabah di Bank Mega Syariah Periode 2016-2024 - Mutawali Mutawali; Mukhooyaroh Mukhooyaroh; Maharani Maharani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study examines the legal protection of children born from unregistered marriages conducted in polygamous relationships without court permission, as reflected in the Decision of the Kudus Religious Court Number 94/Pdt.P/2022/PA.Kds. The issue arises because unregistered marriages often create legal uncertainty regarding the civil status and rights of children, particularly when the father remains legally married to another woman. This research aims to analyze the legal consequences faced by such children and to evaluate the judges’ legal considerations in determining the child’s legal origin. The study employs a normative juridical method using statutory, case, and conceptual approaches through the analysis of legislation, court decisions, and legal doctrines related to marriage and child protection. The findings indicate that children born from unregistered marriages remain biologically connected to both parents, although administrative barriers may hinder the recognition of their civil relationship with the father. The court determination of child origin serves as an important legal instrument to guarantee the child’s rights to identity, maintenance, education, and inheritance. The judges adopted a progressive legal approach by prioritizing the best interests of the child over the formal absence of marriage registration.